Remote sensing products validated by flux tower data in Amazon rain forest - PACA, Victor Hugo da Motta (2022)
This work compares methods of climate measurements, such as those used to measure evapotranspiration, precipitation, net radiation, and temperature. The satellite products used were compared and evaluated against flux tower data. Evapotranspiration was validated against the SSEBop monthly and GLEAM daily and monthly products, respectively, and the results were RMSE = 24.144 mm/month, NRMSE = 0.223, r2 = 0.163, slope = 0.411; RMSE = 1.781 mm/day, NRMSE = 0.599, r2 = 0.000, slope = 0.006; RMSE = 36.17 mm/month, NRMSE = 0.401, r2 = 0.002, and slope = 0.026. Precipitation was compared with the CHIRPS data, K67 was not part of the CHIRPS station correction. The results for both the daily and monthly comparisons were RMSE = 18.777 mm/day, NRMSE = 1.027, r2 = 0.086, slope = 0.238 and RMSE = 130.713 mm/month, NRMSE = 0.706, r2 = 0.402, and slope = 0.818. The net radiation validated monthly with CERES was RMSE = 75.357 W/m2, NRMSE = 0.383, r2 = 0.422, and slope = 0.867. The temperature results, as compared to MOD11C3, were RMSE = 2.829 C, NRMSE = 0.116, r2 = 0.153, and slope = 0.580. Comparisons between the remote sensing products and validation against the ground data were performed on a monthly basis. GLEAM and CHIRPS daily were the data sets with considerable discrepancy.